All‐Fiber Optical Waveform Converter Based on Deformed Catenary Nanostructure. Issue 11 (12th September 2021) - Zhang, Wentao; Luo, Zhongyue; Wang, Rui; Jiang, Xiaowen; Liu, Houquan; Deng, Shijie; Chen, Ming; Yuan, Libo; Deng, Hongchang
Abstract : Herein, an optical waveform converter is presented by using a deformed catenary nanostructure at a double‐cladding fiber end. A vortex beam and Gaussian beam can be generated by wavelength modulation of the helical optical fiber grating fabricated in the double‐cladding fiber. Through the circular polarization modulation of the deformed catenary nanostructure, the generated beams can realize further various waveform conversions, forming several special beams with unique optical focusing, divergence, and rotation capabilities. Taking advantage of the combination of optical fiber integration and metasurface technologies, the device has broad application prospects in biomedicine, optical communication, optical manipulation, and optical imaging. Abstract : Designing an all‐fiber waveform converter by integrating one‐dimensional long helical fiber grating and two‐dimensional deformed catenary nanostructure. Through wavelength and circular polarization modulation, the device has unique ability in optical focusing, divergence, and rotation, which can make the generated light beam break through the diffraction limit. It has potential applications in optical manipulation and imaging.